THE EXERTION DEVELOPMENT OF 1,4-BENZENEDICARBOXYLATE BASED METAL-ORGANIC FRAMEWORKS AND ITS MODIFICATION AS A HIGH PERFORMANCE NON-ENZYMATIC GLUCOSE SENSOR - Gumilar, Gilang
Diabetes is a dangerous disease caused by the body’s inability to produce and use insulin properly, increasing the glucose levels in the blood. Under physiopathological conditions, the concentration of glucose in the blood is 2 – 30 mM. Currently, the technology that is growing fast in glucose detection is biosensors. The most current advanced biosensors are electrochemical and surface plasmon resonance (SPR). However, glucose detection with these techniques still requires enzymes to bound the glucose that makes the sensors expensive, low stable, and requires complex immobilization. As a porous material with an extensive specific area, metal-organic frameworks (MOFs) can capture and localize enzymes or bioreceptors for specific biomolecular targets, which is beneficial in biosensor technology. Unfortunately, the bulk MOFs has low conductivity, and the active site is challenging to access, so it must be functionalized with glucose receptors. In reducing this limitation, the morphology of MOF can be modified into a three-dimensional hierarchical form composed of two-dimensional particles. This research has successfully demonstrated the solvothermal method to synthesize hierarchical plate/sheet-like (HPSL) 1,4- benzenedicarboxylate acid based MOFs with Cu, Mn, Ni, and Zr as the metal center (M-BDC). Electrochemical sensors utilize electrocatalytic properties through oxidation-reduction reactions, while SPR utilizes macromolecular interactions. Therefore, to determine the dominant properties of HPSL M-BDC, which is useful for non-enzymatic glucose sensors, their performance is compared using these two techniques. The result shows that the HPSL M-BDC did not show electrocatalytic activity against glucose on the electrochemical sensor, except for the hierarchical sheet-like (HSL) Ni-BDC with a sensitivity of 635.9 ????A mM-1cm-2 in a concentration range of 0.01 mM – 0.8 mM and had a detection limit (LOD) of 6.68 ????M (S/N = 3). Besides, the selectivity is excellent, and the response time is swift (less than 5 seconds). In the SPR sensor, the HPSL M-BDC is immobilized onto the standard SPR sensor chip using a spin coating (SC) technique. The use of HPSL M-BDC in the SPR technique showed fascinating results where all samples demonstrated a response to glucose. SPR response measurements showed that the sensitivity of Zr- BDC hierarchy plate-like(HPL) > Cu-BDC HPL > Mn-BDC HSL > Ni-BDC HSL. While the LOD obtained, from large to small, is Cu-BDC HPL (10.383 mM) > Ni- BDC HSL (4,945 mM) > Mn-BDC HSL (4,790 mM) in the concentration range of 1 – 20 mM. The LOD of Zr-BDC HPL was 4.499 mM in the concentration range of 0.1 – 20 mM. This data shows that Zr-BDC HPL produces the best performance on the non-enzymatic glucose SPR sensor because it has the highest sensitivity and the lowest LOD. If we compare the performance of M-BDC HPSL on electrochemistry and SPR, the LOD value of Ni-BDC HSL on electrochemistry is smaller than Zr- BDC HPL. However, its working concentration range is far below the range of physiopathological glucose concentrations in blood, so that it is not compatible to be used as a diabetes sensor. The absence of a response to Cu-BDC HPL, Mn-BDC HSL, and Zr-BDC HPL by electrochemical technique, while there is a response using the SPR technique, confirms that M-BDC HPSL specific properties that can be utilized more on SPR sensors through macromolecular interactions of glucose- BDC HPSL. The interaction mechanism can be predicted based on adsorption isotherm, kinetic models, and Fourier transform infrared (FTIR) data. The specific property of M-BDC HPSL has an active site of hydroxyl and carboxyl functional groups that can bind to the glucose hydroxyl group through macromolecular interactions. Therefore, the development of M-BDC HPSL, especially Zr-BDC HPL, as a non-enzymatic glucose sensor is more appropriate by using the SPR technique. Although Zr-BDC HPL performance is good, but it is still lower than other studies. Then, it needs further improvement. Several studies used morphological modification strategies, immobilization techniques, and signal amplification to enhance the performance. This study successfully combined these strategies to produce a high-performance nonenzymatic glucose SPR sensor chip. Modifying the morphology of Zr-BDC HPL into octahedra and optimizing the SC procedure produced a better LOD, which was 0.784 mM in the concentration range of 0.1 – 10 mM. Furthermore, the SPR – Zr- BDC sensor chip performance was also improved by using the direct assembly (DA) immobilization technique. The LOD obtained is 0.389 mM in the range of 0.1 – 10 mM. Lastly, the sensor's performance was improved by hybridizing the Zr-BDC octahedra with gold nanoparticle (AuNp@Zr-BDC) using the solvothermal technique and then immobilized with the DA technique. As a result, the highest performance was shown by the AuNp@Zr-BDC sample with the addition of 0.5 mL AuNp colloid (ZG1). As a result, the obtained LOD value of this sensor chip is 0.0693 mM in the range of 0.01 – 10 mM. In addition, this sensor also has good selectivity and also has better reusability than the previous one.